‘I went there in an effort to help the child, but you can see there is corruption in the world’: Adults’ conceptualisations and enactments of child protection in schools in a challenging context - Ellen Turner; Robert Nyakuwa; Tendai Nhenga-Chakarisa; Charles Muchemwa Nherera; Annah Theresa Nyadombo; Dorcas Mgugu; Caroline Trigg; Camilla Fabbri; Sarah Rank; Karen Devries (PLoS ONE, 2022)
Schools have the potential to be sites of support for vulnerable children, but can also be sites of violence perpetration. In this qualitative study we explore how adult school stakeholders in and around two public Catholic primary schools in Zimbabwe conceptualise and enact child protection. We analysed our findings in light of the protracted economic crisis in Zimbabwe; the current policy context for child protection; and the Covid-19 pandemic. We conducted semi-structured interviews with 18 adult education stakeholders in and around one rural and one urban school in the Harare Archdiocese, from October 2020 to January 2021. This comprised 12 school-level stakeholders, including teachers (N = 4), parents (N = 4), school priests (N = 2), and headteachers (N = 2), who were the main focus of this study, and a further 6 high-level education actors. We employed thematic analysis. Adults in this study placed considerable responsibility on children to protect themselves, with often unreasonably high expectations of children’s capacity to prevent abuse. At times they also blamed and stigmatised children, which was gendered, and particularly emerged around adolescent sexuality. Our findings suggest that this was linked to social norms around discipline, protection and gender, but in particular, the way these emerged in relation to the challenges of the context. Policy and interventions to promote child protection in schools in Zimbabwe should incorporate both an attention to the challenges teachers face in contexts of adversity, as well as address a tendency for adult school stakeholders to hold children responsible for their own protection.